2017
DOI: 10.3389/fpsyg.2017.00329
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Expectations: Examining How Peers Shape Female Students' Intent to Pursue STEM Fields

Abstract: Building on prior psychological and sociological research on the power of local environments to shape gendered outcomes in STEM fields, this study focuses on the critical stage of adolescence to explore the potential negative impact of exposure to exclusionary messages from peers within girls' science classrooms, as well as the positive potential impact of inclusionary messages. Specifically, utilizing longitudinal data from a diverse sample of adolescent youth, analyses examine how the presence of biased male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 52 publications
2
37
1
Order By: Relevance
“…Studies that consider gender norms and focus on a more immediate environment, such as Robnett and Leaper (2013;US), suggest thatin line with H2Agirls are less interested in STEM careers when their friend group does not support STEM and is predominantly comprised of members of the same sex. Other studies, contrary to H2A or H2B, find that a male-dominated environment enforces traditional gender norms among girls (Dasgupta et al, 2015;Riegle-Crumb & Morton, 2017). For instance, Dasgupta et al (2015) concluded from an experiment that implicit masculine stereotypes about engineering led to less engineering career aspirations among women who were assigned to primarily opposite-sex (male-dominated) groups.…”
Section: Friends' Gender Norms and Gender Composition Of The Friend Gmentioning
confidence: 93%
“…Studies that consider gender norms and focus on a more immediate environment, such as Robnett and Leaper (2013;US), suggest thatin line with H2Agirls are less interested in STEM careers when their friend group does not support STEM and is predominantly comprised of members of the same sex. Other studies, contrary to H2A or H2B, find that a male-dominated environment enforces traditional gender norms among girls (Dasgupta et al, 2015;Riegle-Crumb & Morton, 2017). For instance, Dasgupta et al (2015) concluded from an experiment that implicit masculine stereotypes about engineering led to less engineering career aspirations among women who were assigned to primarily opposite-sex (male-dominated) groups.…”
Section: Friends' Gender Norms and Gender Composition Of The Friend Gmentioning
confidence: 93%
“…In addition, most scholars have agreed that local environments and other venues of everyday social interactions such as homes, schools and religious places are the most powerful ways to construct the gender roles (Riegle-Crumb & Morton, 2017). Those places are usually the first venues to construct gender roles and 'subsequently remind' individuals of what is appropriate and expected norms and behaviors of a certain gender (Risman, 2004).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…But to fully support girls from diverse backgrounds, including girls of color in STEM, we need to move beyond inclusion and incorporate culturally responsive teaching (Brown, 2017;Gay, 2013;Ladson-Billings, 2008;. Future stud-they grow older and stereotypes are reinforced by parents, peers and educators (Hazari et al, 2015;Riegle-Crumb and Morton, 2017;Tan et al, 2013). In addition, our culture recognizes certain fields as being legitimate STEM disciplines (e.g.…”
Section: Discussionmentioning
confidence: 99%